2022
DOI: 10.26508/lsa.202201608
|View full text |Cite
|
Sign up to set email alerts
|

Comparative functional genomics identifies unique molecular features of EPSCs

Abstract: Extended pluripotent or expanded potential stem cells (EPSCs) possess superior developmental potential to embryonic stem cells (ESCs). However, the molecular underpinning of EPSC maintenance in vitro is not well defined. We comparatively studied transcriptome, chromatin accessibility, active histone modification marks, and relative proteomes of ESCs and the two well-established EPSC lines to probe the molecular foundation underlying EPSC developmental potential. Despite some overlapping transcriptomic and chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 64 publications
0
1
0
Order By: Relevance
“…In parallel with the cross-platform comparison, we also analyzed the genomic impact of the RUNX3 and ZBTB46 on the global gene expression profile of ESCs. The transcriptional landscape of the murine ESCs has been intensively studied using bulk or single-cell mRNA sequencing (Lienert et al, 2011;Kumar et al, 2014;Kolodziejczyk et al, 2015;Malik et al, 2022). Interestingly, it was observed that the gene expression pattern of the murine ESCs is heterogeneous and stochastic; moreover, it is depending on the cell culture conditions (Kumar et al, 2014;Torres-Padilla and Chambers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the cross-platform comparison, we also analyzed the genomic impact of the RUNX3 and ZBTB46 on the global gene expression profile of ESCs. The transcriptional landscape of the murine ESCs has been intensively studied using bulk or single-cell mRNA sequencing (Lienert et al, 2011;Kumar et al, 2014;Kolodziejczyk et al, 2015;Malik et al, 2022). Interestingly, it was observed that the gene expression pattern of the murine ESCs is heterogeneous and stochastic; moreover, it is depending on the cell culture conditions (Kumar et al, 2014;Torres-Padilla and Chambers, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with the cross-platform comparison, we also analyzed the genomic impact of the RUNX3 and ZBTB46 on the global gene expression pro le of ESCs. The transcriptional landscape of the murine ESCs has been intensively studied using bulk or single cell mRNA sequencing [27][28][29][30] . Interestingly, it was observed that the gene expression pattern of the murine ESCs is heterogeneous and stochastic, moreover, it is depending on the cell culture conditions 27,31 .…”
Section: Discussionmentioning
confidence: 99%